Stratification of patients with Menière’s disease based on eye movement videos recorded from the beginning of vertigo attacks and contrast-enhanced MRI findings - Ueno, Yuya; Imai, Takao; Higashi-Shingai, Kayoko; Ohta, Yumi; Sato, Takashi; Kamakura, Takefumi; Ozono, Yoshiyuki; Inohara, Hidenori (Frontiers in Neurology, 2024)
Purpose: Diagnosis of Menière's disease (MD) relies on subjective factors and the patients diagnosed with MD may have heterogeneous pathophysiologies. This study aims to stratify MD patients using two objective data, nystagmus videos and contrast-enhanced magnetic resonance imaging (CE-MRI).Methods: This is a retrospective cross-sectional study. According to the Japan Society for Equilibrium Research criteria (c-JSER), adults diagnosed with definite MD and who obtained videos recorded by portable nystagmus recorder immediately following vertigo attacks and underwent CE-MRI of the inner ear were included (n = 91). Patients who obtained no nystagmus videos, who had undergone sac surgery, and those with long examination intervals were excluded (n = 40).Results: The gender of the subjects was 22 males and 29 females. The age range was 20-82 y, with a median of 54 y. Endolymphatic hydrops (EH) were observed on CE-MRI in 84% (43 patients). Thirty-one patients had unilateral EH. All of them demonstrated EH on the side of the presence of cochlear symptoms. The number of patients who had both nystagmus and EH was 38. Five patients only showed EH and 5 patients only exhibited nystagmus, while 3 patients did not have either. Of the 43 nystagmus records, 32 showed irritative nystagmus immediately after the vertigo episode. The direction of nystagmus later reversed in 44% of cases over 24 hours. Conclusion: Patients were stratified into subgroups based on the presence or absence of EH and nystagmus. The side with cochlear symptoms was consistent with EH. The c-JSER allows for the diagnosis of early-stage MD patients, and it can be used to treat early MD and preserve hearing; however, this approach may also include patients with different pathologies.